A visual framework for software requirements traceability - Abdulkadir Ahmad Madaki; Wan Mohd Nazmee Wan Zainon (Bulletin of Electrical Engineering and Informatics, 2022)
Requirement traceability supports several activities of software development processes such as impact analysis, requirement changes, maintenance, verification, and validation of a software system. For its effective use in those activities, the graphical representation of traceability data plays an important role. However, several traceability tools lack an excellent visual representation to present these type of data. Therefore, this paper presents a visual framework which has been designed and proposed as a prototype tool that can visualize traceability data. The framework applies data visualization techniques to represent requirements and its artefacts relationships as colour-coded symbols on a node-link diagram; users can traverse the graph with an impact analysis method to understand data and make decisions. The evaluation result shows that the proposed tool is useful and easy enough in terms of improving user interaction and to better understand requirement traceability data.